Improving Customer Loyalty Through Experiental Value, Service Quality And Trust - Rifki Arikah An Namla; Sukaris Sukaris; Budiyono Pristyadi; Al Kusani Al Kusani (INNOVATION RESEARCH JOURNAL, 2020)
Customer with high loyalty are the assets of the company because they will provide positive recommendations and indirectly will invite people around to determine and use the product of the service company they use. This research aims to find out whether there is an effect of experiential value, service quality and trust on customer loyalty indihome in Gresik regency. Sampling is used Non Probability Sampling by using Ferdinand formula, where the sample amount is 100 people. The analysis used in this study is multiple linear regressions. The results are proven to show that experiential value, service quality and trust have a positive and significant effect on customer loyalty in Gresik regency